Cyanobacteria 2018
DOI: 10.5772/intechopen.79750
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Cyanobacteria on Limestone Caves

Abstract: The caves are the biodiversity centers for different types of microorganisms, especially for cyanobacteria. They are also present in almost all extreme environments, and their importance in terrestrial ecosystems is greater because of the decreased competition from vascular plants. Cyanobacteria occurring on rocks are epilithic (colonizing the substrate surface), hypolithic (growing under pebbles and small stones), and endolithic (present in an upper layer of rock). There are three limiting factors for cyanoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The morphological and/or genetic identifications of phototrophs with FaRLiP capacity (e.g. Leptolyngbya , Chroococcidiopsis ) in other limestone environments such as Mayan ruins (McNamara et al ., ), caves (Lamprinou et al ., ; Joanna and Andrzej, ) and hypogean catacombs (Gabrielle et al ., ) would suggest that limestone surfaces are particularly suitable habitats for cyanobacteria with Chl d / f , possibly due to material‐specific reflectance properties, which could produce spectrally induced stratifications similar to those found in aquatic ecosystems (Stomp et al ., ). We note that limestone has comparable spectral properties with other rock materials (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological and/or genetic identifications of phototrophs with FaRLiP capacity (e.g. Leptolyngbya , Chroococcidiopsis ) in other limestone environments such as Mayan ruins (McNamara et al ., ), caves (Lamprinou et al ., ; Joanna and Andrzej, ) and hypogean catacombs (Gabrielle et al ., ) would suggest that limestone surfaces are particularly suitable habitats for cyanobacteria with Chl d / f , possibly due to material‐specific reflectance properties, which could produce spectrally induced stratifications similar to those found in aquatic ecosystems (Stomp et al ., ). We note that limestone has comparable spectral properties with other rock materials (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphasic taxonomy applied to the strains of this study revealed taxa known to be part of bloom-forming communities (Sphaerospermopsis and Nodularia), rock-dwelling communities (Scytonema and Tolypothrix), and hot spring cyanobacteria mats (Desertifilum and Gloeotrichia) (Dadheech et al, 2014;Mazur-Marzec et al, 2015;Gkelis et al, 2017;Joanna and Andrzej, 2018).…”
Section: Biodiversitymentioning
confidence: 94%
“…Cyanobacteria are considered the pioneering inhabitants in cave colonization (Joanna and Andrzej, 2018). They prevail in the cave entrances compared to the other microalgae (Mulec and Kosi, 2009) by colonizing various parts of the cave entrances, where biodiversity is the lowest (Vinogradova N. et al, 1998).…”
Section: Biodiversitymentioning
confidence: 99%
“…The polyphasic taxonomy applied to the strains of this study revealed taxa known to be part of bloom-forming communities ( Sphaerospermopsis and Nodularia), rock-dwelling communities ( Scytonema and Tolypothrix ), and hot spring cyanobacteria mats ( Desertifilum and Gloeotrichia ) (Dadheech et al, 2014; Mazur-Marzec et al, 2015; Gkelis et al, 2017; Joanna and Andrzej, 2018). Our results revealed the presence of taxa not previously described from Greek habitats (Gkelis et al, 2016), such as Allinostoc (Saraf et al, 2018) and Oculatella (Osorio-Santos et al, 2014) and taxa previously described only from the tropical zone like Komarekiella and Kovacikia (Miscoe et al, 2016; Hentschke et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…were isolated from extensive dark-green coverings dominated by cyanobacteria like Phormidium , Tolypothrix, Scytonema , and Geitleria species. Cyanobacteria are considered the pioneering inhabitants in cave colonization (Joanna and Andrzej, 2018). They prevail in the cave entrances compared to the other microalgae (Mulec and Kosi, 2009) by colonizing various parts of the cave entrances, where biodiversity is the lowest (Vinogradova N. et al, 1998).…”
Section: Discussionmentioning
confidence: 99%